DIEL VARIATION OF pH AND DISSOLVED OXYGEN IN DIFFERENT FERTILZED FISHPONDS BUILT ON ACID SULPHATE SOILS - Husnah Husnah (Indonesian Fisheries Research Journal, 1995)
An experiment in order to know the effect of fertilizers on diel variation of pH anddissolved oxygen (DO) in pondw.ter was carried out for t6 weeks in acid sulphate soilfrcshwater fisiponds at the Research Station For Freshwater Fisheries Kertamulia, South Sumetra, Indonesia